Observation of the Compatibility of Science Laboratory in Junior High Schools in Samarinda - Akmal Raiky Aryaputra; Wahyu Nur Latifah; Salwa Nadzifa; Enjel Pratiwi; Annisa Salsabila; Greny Mispi Anisa Sari; Nurul Fitriyah Sulaeman (Universitas Lambung Mangkurat, 2023)
A laboratory is a place with quantitatively and qualitatively complementary and adequate equipment for applying scientific theories, theory testing, certification exams, research, and others. In relation to school education, the science laboratory serves as a place of practical learning in chemistry, biology, and physics that requires special equipment. The purpose of this study was to determine the completeness of the junior high school science laboratory in Samarinda following the criteria of the science laboratory. The method used in this study is qualitative, namely by interview and observation. Based on the survey results, there are differences in the suitability of the places in the two schools; in school A, the suitability of the science laboratory premises meets the existing criteria, and in school B the science laboratory room is still appropriate. However, it does not meet the existing criteria, so it needs to be repaired and added facilities. Given the importance of the science laboratory's function, the laboratory room's suitability needs to be continuously improved.